Прогностичко значење на квантитативниот хбс-антиген и квантитативната хбв днк и нивната корелација кај пациенти со хронична хепатитис б-вирусна инфекција - Димзова, Марија (Медицински факултет, УКИМ, Скопје, 2018)
Introduction: Chronic infection with hepatitis B virus (HBV) is a global health problem, with over 350 million people worldwide affected by it, remaining the predominant cause of chronic liver disease and liver-related morbidity worldwide. This clinical condition is considered to be the major risk factor for cirrhosis, end-stage liver disease and hepatocellular carcinoma (HCC). The natural history of chronic hepatitis B (CHB) is complex and consists of several phases. The infected patients can go through different phases during their disease. These phases differ between each other in terms of HBV DNA serum levels, the extent of liver diseases and disease progression towards liver fibrosis, which can be gradual, accelerated and sporadic. The phases in the natural history of chronic hepatitis B are of great significance, not only in the clinical approach to the patient, but also in decision making for liver biopsy and starting antiviral therapy in order to prevent the development of CHB caused complications. It is not always easy to distinguish between these clinical phases. This is especially true for HBeAg-negative CHB patients with active hepatic necrotic inflammation and persistent viraemia, with higher rates of complications in contrast to patients with CHB who are inactive carriers. Both forms of HBeAg negative CHB have similar laboratory and serologic characteristics and are not always easy to distinguish. This imposes the need for establishing non-invasive procedures which will help to differentiate between these two phases, and at the same time will reflect the liver histology. One of these non-invasive markers is the serum level of HBs antigen, quantitative HBsAg (qHBsAg, HBsAgQ). Aims: 1. To determine the correlation between quantitative HBsAg and HBV DNА, quantitative HBsAg and ALT, quantitative HBsAg and liver injury in patients with HBeAg negative chronic HBV infection (inactive carriers) and patients with HBeAg negative chronic hepatitis B (HBeAg (-) CHB). 2. To determine the diagnostic numeric value of quantitative HBsAg in patients with chronic hepatitis B. 3. To determine the diagnostic significance of quantitative HBsAg in the differentiation of the patients with HBeAg negative chronic HBV infection (inactive carriers) and patients with HBeAg negative chronic hepatitis B (HBeAg (-) CHB). Material and methods: The study was conducted at the University Clinic for infectious diseases and febrile conditions, Skopje as a prospective, non-randomized study of treatment naïve patients with serologically confirmed chronic hepatitis B viral infection. The study included 109 patients over 18 years of age, patients with signed informed consent, and patients with serologically confirmed hepatitis B surface antigen (HBsAg) in a period of at least six months, patients who were HBeAg negative, patients who have been observed in at least two occasions, with a minimum period of follow-up of at least 6 months. The exclusion criteria were co-infection with human immunodeficiency virus (HIV), hepatitis A (HAV) and hepatitis C (HCV). The patients were divided in two groups: 56 patients with HBeAg negative chronic HBV infection (inactive carriers-IC) and 53 patients with HBeAg negative chronic hepatitis (HBeAg - CHB). All data were processed using a statistical computer program Statistica 7.1 for Windows and SPSS Statistics 17.0. Results: there are no significant differences in terms of gender but patients with HBeAg (-) CHB are significantly older than patients who are inactive carriers. The serum level of quantitative HBsAg in patients with HBeAg (-) CHB is significantly higher than in inactive carriers (IC) patients (p=0,000), as well as the level of HBV DNA (p=0,000). The value of qHBsAg varies in the interval 2753,73±4701,29 IU/ml, and of HBV DNA in the interval 727,95±584,24 IU/ml for IC. In patients with HBeAg (-) CHB qHBsAg varies in the interval 2556,06±27188,85 IU/ml, and HBV DNA varies in the interval 7237363,98±46513427,91 IU/ml. There is moderately week positive correlation (R=0,18; p>0,05) between qHBsAg and HBV DNA in IC group, while in patients with HBeAg (-) CHB this correlation is moderately strong (R=0,25, p>0,05). The numeric diagnostic value for qHBsAg varies in the interval 332,03±259,45 IU/ml; with optimal cut off value for qHBsAg of 0,501. Patients with qHBsAg above 1000 IU/ml have 0,12 times lower chance to be inactive hepatitis B carriers and 8,41 times higher chance to have HBeAg (-) CHB in contrast to patients whose qHBsAg level is lower than 1000 IU/ml. The predictive probability of quantitative HBsAg is 13,37; patients with quantitative HBsAg above 1000 IU/ml have 0,113 times lower chance for inactive carrier state; and 8,83 times higher chance for HBeAg negative chronic hepatitis state in contrast to patients with qHBsAg bellow 1000 IU/ml (p<0,001). For Fisher’s Exact Test, there is significant differences in the ultrasonography of the liver (p=0,004), and the severity of fibrosis (p=0,006) between the patients with HBeAg negative CHB and inactive cariers. Conclusion: there is positive correlation between quantitative HBsAg and HBV DNA in both groups of patients. Quantitative HBsAg has greater predictive power in discrimination of the disease phases in patients with CHB compared to that of HBV DNA. Fibrosis as a form of liver injury is greater in patients with qHBsAg > 1000 IU/ml. Quantitative HBsAg can be used by itself for evaluation and monitoring of patients with CHB. Quantitative HBsAg can be used as an alternative independent biomarker for discrimination of patients who are inactive carriers from patients with HBeAg (-) CHB.
Докторска дисертација одбранета во 2018 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Ирена Кондова Топузовска.
Keywords: hepatitis B, inactive carrier, HBeAg negative chronic hepatitis, quantitative HBsAg, HBV DNA, hepatitis Be antigen, anti HBe antigen